Departure from Orientalist Norms in Arminius Vambery’s Travels in Central Asia - Gholi, Ahmad; Mosaabad , Masoud Ahmadi (Dirasat: Human and Social Sciences, 2024)
Objectives: This article critiques Edward Said’s Orientalism through a detailed examination of Arminius Vambery’s "Travels in Central Asia" as a departure from traditional Western travel writing. By analyzing Vambery’s work, the aim is to highlight instances where he deviates from the established principles of Orientalism. Methods: Drawing on Behdad’s insights, this study explores the dynamic and flexible nature of Orientalist discourse. It investigates how travel writers like Vambery can deviate from the norms and conventions of Orientalism in their encounters with Eastern cultures and people. Results: The findings of this study demonstrate three notable instances where Vambery showcases his departure from Orientalism. Firstly, he recounts an encounter with two Afghans who discover his disguise during their shared journey. Secondly, Vambery refrains from depicting the harem of local Emirs in Turkistan as a place of hedonism, in contrast to prevailing Victorian travel writers. Lastly, he appreciates and celebrates the local cuisine, in contrast to the dismissive attitudes prevalent among his contemporaries. Conclusions: It is a mistaken assumption that Victorian travel writers exclusively followed Orientalist tropes when exploring the Islamic Orient. The study emphasizes the importance of recognizing these counter-Orientalist moments in travel literature to present a more nuanced and comprehensive understanding of the works.